2018
DOI: 10.1038/s41598-018-32036-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of blood pulsations parameters in carotid basin due to body position change

Abstract: The velocity of the pulse wave (PWV) propagating through the vascular tree is an essential parameter for diagnostic the state of the cardiovascular system especially when it is measured in the pool of carotid arteries. In this research, we showed for the first time that the time of the blood-pressure-wave propagation from the heart to the face is a function of the body position. Significant asymmetry and asynchronicity of blood pulsations in the facial area were found in a recumbent position. Parameters of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
0
34
0
1
Order By: Relevance
“…This illumination was chosen because several research groups working with the reflection-mode PPG reported that the largest intensity modulation at the heartbeat frequency was observed at the green light modulation (Verkruysse et al, 2008; Kamshilin et al, 2011; Fallow et al, 2013). PPG-system design was described in details in our recent paper (Kamshilin et al, 2018). Briefly, it consists of a digital monochrome CMOS camera (10-bit model GigE uEye UI-5220SE of the Imaging Development Systems GmbH) integrated with an illuminator with a polarization filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This illumination was chosen because several research groups working with the reflection-mode PPG reported that the largest intensity modulation at the heartbeat frequency was observed at the green light modulation (Verkruysse et al, 2008; Kamshilin et al, 2011; Fallow et al, 2013). PPG-system design was described in details in our recent paper (Kamshilin et al, 2018). Briefly, it consists of a digital monochrome CMOS camera (10-bit model GigE uEye UI-5220SE of the Imaging Development Systems GmbH) integrated with an illuminator with a polarization filter.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate CBF dynamics we used an amplitude of the pulsatile component (APC) of the photoplethysmographic waveform that shows modulation of the light reemitted from the brain at the heartbeat frequency (Allen, 2007). Spatial distribution of APC over the cortex was calculated using an algorithm described in details in our recent paper (Kamshilin et al, 2018). Briefly, the algorithm includes the following steps.…”
Section: Methodsmentioning
confidence: 99%
“…Recorded video, ECG and temperature data were processed by using custom software implemented in the MATLAB ® platform. The algorithm of PPG signal processing was described in detail in our previous papers [14,19]. Briefly, we calculated the spatial distribution of the blood pulsation amplitude (BPA) over the facial area.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature data were recorded every 2 s synchronously with the recording of video frames. A detailed description of the experimental setup is given in our recent paper [14]. Video frames, ECG and temperature data were downloaded to the computer's hard drive for subsequent offline processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation